Methodological Comparison of Gene Expression Detection: qPCR vs. Immunocytochemistry in Ovarian Cancer Models (Comprehensive Journal of Science, 2025)
Reliable biomarker detection remains a major challenge in epithelial ovarian cancer (EOC), particularly for early diagnosis. Both quantitative real-time PCR (qPCR) and immunocytochemistry (ICC) are widely employed to assess gene expression, yet their diagnostic consistency and relative utility have not been systematically compared in the same experimental setting. Methods: The expression of LPAR1, LPAR2, and selected HDAC isoforms (HDAC1, HDAC3, HDAC5, and HDAC6) was evaluated in ovarian cancer cell lines (SKOV3 and OAW42) and normal human ovarian epithelial cells (HOSEpiC). qPCR quantified relative mRNA levels, while ICC determined protein localization and semi-quantitative analysis based on staining intensity. Comparative analyses focused on the sensitivity, consistency, and complementarity of the two methods. Aim: To compare qPCR and ICC in assessing gene expression in ovarian cancer, focusing on their sensitivity, consistency, and complementary value for biomarker validation. Results: qPCR revealed significant upregulation of LPAR1, LPAR2, HDAC1, HDAC3, HDAC5, and HDAC6 in SKOV3 cells, while OAW42 cells showed variable or downregulated expression. ICC confirmed protein expression for most targets but showed discrepancies with qPCR in some cases (e.g., LPAR2 downregulated in ICC despite qPCR upregulation). Overall, qPCR provided higher sensitivity for low-abundance transcripts, whereas ICC provided spatial localization at the protein level. Conclusion: qPCR and ICC offer complementary insights into gene expression in ovarian cancer. While qPCR is more sensitive for quantification, ICC adds critical value in visualizing protein localization. The combined use of both techniques enhances biomarker validation and could strengthen diagnostic strategies for EOC.
Keywords: Ovarian cancer, qPCR, Immunocytochemistry, Biomarkers, LPA receptors, HDACs, diagnostic consistency.